SMART CAMPUS: A REVIEW ON SMART ATTENDANCE SYSTEMS AS AN EFFICIENT APPROACH - RASHID, AIDA MARYANI (Journal of Engineering & Technological Advances, 2024)
Smart attendance systems that utilize advanced technologies such as RFID, BLE, and NFC have been developed to provide more efficient and accurate way of tracking attendance with real-time monitoring and tracking capabilities. The implementation of smart attendance systems can help universities stay relevant and competitive in the future as the world becomes more interconnected and technology-driven. This paper provides an overview and study on the benefits of smart attendance systems and a comprehensive analysis of the different types of systems currently being used by universities worldwide. Overall, this paper contributes to the body of knowledge on smart attendance systems and their potential impact on the educational sector.